Affection, self-esteem, and resilient coping as predictors of health in old age - Soares, Inês Isabel Xavier (2015)
The present dissertation, titled Affection, self-esteem, and resilient coping as predictors of health in old age arises in the context of the Masters in Clinical Psychology and Health, after noticing the lack of studies covering such variables. Hence, the following objectives were estabilished: (1) Evaluate, on a group of elderly, the levels of affection, self-esteem, resilient coping and health; (2) Evaluate, comparing differences between genders; (3) Determine the impact in terms of psychosocial and sociodemographic variables, in the overall health of the elderly; and (4) determine the degree of association between the variables. It is an integral part of this dissertation, an article, written in English, submitted to publication in the journal Clinical Gerontologist , which represents a methodological contribution to a greater understanding of the psychosocial variables linked to a more positive aging . In order to theoretically deepen the variables being studied, this dissertation, even presents an organized theoretical attachment in order to enable the reader to consolidate any aspects which, due to their nature, were not developed in the theoretical article. The achieved results show that high levels of positive affection, self-esteem and resilient coping are strongly connected to a better general health levels, and particularly, to higher levels of emotional well-being. Though, the negative affection is related to worse health status, which demonstrates the importance of positive emotions on the health of the elderly.